Investigation of a cluster of pituitary adenomas in workers in the aluminum industry. Issue 11 (November 1996) - Cullen, M R; Checkoway, H; Alexander, B H
Abstract : OBJECTIVE: Four cases of pituitary adenoma among employees at a primary aluminum production factory were identified over a five year period by a community physician. The objective of this investigation was to determine whether there has been a comparable high incidence in other aluminum factories, and if particular jobs, departments, or activities in the industry are associated with higher rates of the disease. METHOD: Pituitary adenoma in employees at all United States factories of the company for the years 1989-94 was assessed by a search of a health data information bank and an insurance data base covering present and past employees of the corporation. The incidence in the aluminum workers was estimated and compared with the workers in the index plant. A nested case control study was conducted to compare employment histories of identified cases with those of age and sex matched controls selected from the health information data base. RESULTS: 25 cases, including the index cases, were identified which had been diagnosed during the period 1989-94. The resulting rate of 10.4/100, 000 person-years was much lower than that at the index plant. Case-control analysis showed no coherent pattern of location, department, or job significantly associated with risk. In particular, jobs and departments associated with exposures common to aluminum smelting-such as coal tar pitch volatiles and fluorides-were shown to be uncommon among cases compared with age and sex matched controls. CONCLUSION: Overall, despite the unprecedented cluster at a single plant, no strong evidence was found that the rate of pituitary adenoma is increased in aluminum workers generally. We found no association with any work activity or location in the industry to suggest a work related or exposure related cause for the disease.